Effect of Process Parameters on NaOH Catalysed Cassava Starch Modification - Ameh , A. O.; Oguche, J. E.; Bashayi , B. M. (Nigerian Journal of Pharmaceutical and Applied Science Research, 2020)
This paper reports a study on the effect of process parameters on NaOH catalysed cassava starch modification using sodium acetate as crosslinking agent as well as to optimize the process using Response Surface Methodology (RSM). Central composite design (CCD) was employed to determine the effect of process parameters: sodium hydroxide catalyst (2g-8g), reaction temperature (65 - 85 oC) and reaction time (50- 70 min), on gelatinization temperature and pH of modified cassava starch. The regression analysis showed good fit of the experimental data to the second-order polynomial (Quadratic models) for the two responses with coefficients of determination (R2) value of 0.8907 and model F-value of 9.05 for gel temperature and (R2) value of 0.8705 and model F-value of 7.47 for pH respectively. The models were found to be significant as its Predicted R2 of 0.8907 was in close agreement with the Adjusted R2 of 0.7923 for gelatinization temperature and Predicted R2 of 0.8705 was in close agreement with the Adjusted R2 of 0.7539 for pH respectively. A good fit of the model was further validated as the lacks of fit values for the two models were found to be greater than 5%. The conditions for modification of cassava starch were predicted by the model at optimum condition: reaction temperature of 68.77oC, sodium hydroxide catalyst of 4.16 g and reaction time of 50 min. with predicted gelatinization temperature and pH of 74.39 oC and 9.85 respectively. Validation experiments conducted at this optimum conditions gave an experimental value of 74 oC of gelatinization temperature and pH of 8.0 respectively which was in close agreement with the predicted values.